Analyzing the Availability of Lexicon in Mathematics Education Using no Traditional Technological Resources - MarÃa Elsa Del Valle; Pedro Salcedo; Anita Ferreira (International Journal of Supply Chain Management, 2016)
To learn mathematics is somehow difficult to most students in different educational levels. There exists a cultural presumption that it happens and therefore the motivation to learn mathematics is low. In national and international tests Chile performs poorly. Researchers suggest different variables to explain this situation. Additionally, there exist work propositions in development. One of these is to use technological support to improve the students' results regarding mathematics especially in the school system. This paper describes a research from 2012 until today focused in the available lexicon of mathematics on secondary school and university students in the 8 Region of the country as an important variable that affects significantly mathematics learning. Data about the available lexicon was obtained after the application of the Test of Lexical Availability. Furthermore, to analyze the obtained data, Lexmath is created. Lexmath is an adaptive hypermedia that employs Excel, graphs theory and Gephi software to establish the available lexicon in which mathematics learning is developed and the need to improve it using this software.